Resistance to the Antimicrobial Agent Fosmidomycin and an FR900098 Prodrug through Mutations in the Deoxyxylulose Phosphate Reductoisomerase Gene (dxr) - Armstrong, Christopher M. (Antimicrob Agents Chemother, 2015)
There is a pressing need for new antimicrobial therapies to combat globally important drug-resistant human pathogens, including Plasmodium falciparum malarial parasites, Mycobacterium tuberculosis, and Gram-negative bacteria, including Escherichia coli. These organisms all possess the essential methylerythritol phosphate (MEP) pathway of isoprenoid biosynthesis, which is not found in humans. The first dedicated enzyme of the MEP pathway, 1-deoxy-d-xylulose 5-phosphate reductoisomerase (Dxr), is inhibited by the phosphonic acid antibiotic fosmidomycin and its analogs, including the N-acetyl analog FR900098 and the phosphoryl analog fosfoxacin. In order to identify mutations in dxr that confer resistance to these drugs, a library of E. coli dxr mutants was screened at lethal fosmidomycin doses. The most resistant allele (with the S222T mutation) alters the fosmidomycin-binding site of Dxr. The expression of this resistant allele increases bacterial resistance to fosmidomycin and other fosmidomycin analogs by 10-fold. These observations confirm that the primary cellular target of fosmidomycin is Dxr. Furthermore, cell lines expressing Dxr-S222T will be a powerful tool to confirm the mechanisms of action of future fosmidomycin analogs.